P4_8 Plasma Windows - Tilley, Frederick; Davis, Claire; Hague, Pete (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The physics behind plasma windows are explored and it is investigated whether they would be applicable on a large scale as a divider between a vacuum and a pressurised hangar. It is found that while possible, it may be difficult due to the large energy need to ionise the plasma and the large scale nature of the magnetic field.